Relationship between Economic Growth and Social Equity in Vietnam after Innovating Nearly Thirty Years - Tinh, Do Phu Tran; Nen, Nguyen Van; Huyen, Nguyen Thanh; Duyen, Pham My (Journal of Asian Business Strategy, 2014)
This paper focuses on analyzing the achievements and limitations of Vietnam for the implementation of social inequality and equity in the economic growth process after renovation in 1986. Economic growth generated the capital to invest the social safe plans, generated more income for people and generated more opportunities to help the people approaching a prosperous life. However, beside above achievements, there are many limitations such as: unsustainable development in income, life standard and poverty alleviation; shortfall amount and bad quality in health care, education and entertainment services… Basing on analyzing the causes of the limitations, the paper proposed the orientations for solving the relationship between the economic growth and social equality in Vietnam next time.